Growing Up Poor: Examining the Link Between Persistent Childhood Poverty and Delinquency - Jarjoura, G. Roger (Journal of quantitative criminology, 2002)
Findings from aggregate-level and ethnographic research suggest that poverty and delinquency are related. The inability of individual-level quantitative research to demonstrate consistent evidence of this relationship, however, has been used to call into question whether poverty is indeed related to an increased propensity for delinquent involvement. This may be due to the difficulty individual-level analyses have in identifying the group most important in uncovering the relationship of poverty to delinquency—those individuals that experience persistent childhood poverty. This paper provides an assessment of the effects of both the level of exposure to poverty and its timing on delinquent involvement using fourteen years of longitudinal data for a national sample of younger adolescents. Findings indicate that exposure to poverty and the timing of such exposure are indeed related to an increased likelihood of involvement in delinquency.